2017
DOI: 10.2147/jpr.s143500
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of the conversion of paracetamol to AM404 in human cerebrospinal fluid

Abstract: Paracetamol is arguably the most commonly used analgesic and antipyretic drug worldwide, however its mechanism of action is still not fully established. It has been shown to exert effects through multiple pathways, some actions suggested to be mediated via N-arachidonoylphenolamine (AM404). AM404, formed through conjugation of paracetamol-derived p-aminophenol with arachidonic acid in the brain, is an activator of the capsaicin receptor, TRPV1, and inhibits the reuptake of the endocannabinoid, anandamide, into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 21 publications
0
24
0
3
Order By: Relevance
“…In both cases, paracetamol's analgesic activity was prevented [23]. In 2017, Sharma et al proved that paracetamol is metabolized in vivo to N-arachidonoylaminophenol (AM404) [24], which is the anandamide reuptake inhibitor [25], as well as weak CB1 [26] and TRPV1 agonist [27]. Another analgesic, metamizole (dipyrone), was also found to act via ECS [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, paracetamol's analgesic activity was prevented [23]. In 2017, Sharma et al proved that paracetamol is metabolized in vivo to N-arachidonoylaminophenol (AM404) [24], which is the anandamide reuptake inhibitor [25], as well as weak CB1 [26] and TRPV1 agonist [27]. Another analgesic, metamizole (dipyrone), was also found to act via ECS [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…1,86,87 In the CNS, as a result of deacetylation and later conjugation with AA by CNS FAAH, a paracetamol metabolite AM404 is generated, first evidenced in humans in 2017. 88,89 It was shown that AM404…”
Section: Endocannabinoid System-dependent Actionmentioning
confidence: 99%
“…Paracetamol has antipyretic and analgesic effects but is not an anti-inflammatory agent. It has only central analgesic effects mediated by its active metabolite N -arachidonoyl-phenolamine (AM404), which forms in the CNS and acts as an anandamide reuptake inhibitor in the dorsal horn of the spinal cord [ 24 ]. It should be considered a first-level agent for reducing pain transmission at the spinal level.…”
Section: Managementmentioning
confidence: 99%